2014
DOI: 10.1038/srep05855
|View full text |Cite
|
Sign up to set email alerts
|

Combined Application of NMR- and GC-MS-Based Metabonomics Yields a Superior Urinary Biomarker Panel for Bipolar Disorder

Abstract: Bipolar disorder (BD) is a debilitating mental disorder that cannot be diagnosed by objective laboratory-based modalities. Our previous studies have independently used nuclear magnetic resonance (NMR)-based and gas chromatography-mass spectrometry (GC-MS)-based metabonomic methods to characterize the urinary metabolic profiles of BD subjects and healthy controls (HC). However, the combined application of NMR spectroscopy and GC-MS may identify a more comprehensive metabolite panel than any single metabonomic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 40 publications
2
62
0
Order By: Relevance
“…One study combined NMR and GC–MS platforms to generate a panel of five urinary metabolite biomarkers for Bipolar Disorder (BD) (four GC–MS-derived and one NMR-derived). 86 This composite biomarker panel discriminated BD subjects from healthy controls with impressive area under the receiver operating characteristic curve (AUC) values of 0.974 in a training set and 0.964 in a test set, which is significantly superior to the previous single platform-derived metabolite panels. Urinary metabolic profiles of renal transplant patients with major injury factors at critical stages following transplantation were investigated by combining NMR and GC–MS.…”
Section: Combining Nmr and Msmentioning
confidence: 90%
“…One study combined NMR and GC–MS platforms to generate a panel of five urinary metabolite biomarkers for Bipolar Disorder (BD) (four GC–MS-derived and one NMR-derived). 86 This composite biomarker panel discriminated BD subjects from healthy controls with impressive area under the receiver operating characteristic curve (AUC) values of 0.974 in a training set and 0.964 in a test set, which is significantly superior to the previous single platform-derived metabolite panels. Urinary metabolic profiles of renal transplant patients with major injury factors at critical stages following transplantation were investigated by combining NMR and GC–MS.…”
Section: Combining Nmr and Msmentioning
confidence: 90%
“…However, there are still no objective laboratory tests to help clinicians in the diagnosis of MDD, although many studies have been done to develop these tests 46. Our group has conducted many studies for identifying potential biomarkers for MDD diagnosis using metabolomics,79 which is used to identify novel biomarkers for various disease states 1012. Another dilemma about the prevention and treatment of MDD is that no existing antidepressants could treat MDD patients with 100% response rate.…”
Section: Introductionmentioning
confidence: 99%
“…Such studies have suggested the possibility of identifying biomarkers for schizophrenia [47,48,49,50,51,52], major depressive disorder [53,54] and posttraumatic stress disorder [55], and have also been used to study medication-induced metabolic changes [56,57]. In bipolar disorder, metabolomic studies have been undertaken in urine samples to identify potential biomarkers [58,59,60,61]. We report our findings from unbiased metabolic profiling of fibroblasts from patients with bipolar disorder and healthy controls, under normal growth conditions as well as under physiologic perturbations.…”
Section: Discussionmentioning
confidence: 99%